(untitled) (Journal of Forensic Medicine & Toxicology, 2020)
Rodent control is important for survival and health of human populations and use of chemical rodenticides is one of the common methods of control. Yellow phosphorus is a highly toxic compound which is used as rodenticide and in firecrackers. This is a prospective observational study conducted on patients admitted to a tertiary care hospital with suspected rodenticide poisoning. The most common age group was 15-30 years with a male preponderance. The most common type of rodenticide consumed was found to be yellow phosphorus. In about three-quarters (72%) of the patients, the rodenticide was procured from grocery stores. In 32.4% of cases domestic fight was the reason for consuming the rodenticide.